Resource-Saving Technique of Hydraulic Calculation of Distributing Gas-Systems - A. Y. Savastsiyonak (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
It is possible to consider a hydraulic calculation technique of distributing gas-systems as a combination of factors that influence on the cost of construction and maintenance of gas-distributing system. The paper contains proposal of a new specification of economic distribution of calculated pressure differential in the system sections; optimum initial flow distribution from the point of view of reliability and economy and taking into account linkage of system rings.The program of hydraulic calculation of low-pressure distributing gas-systems has been developed. While calculating combined systems consisting of steel and polyethylene gas lines reduction in discounted expenses constitutes up to 4 %.